Central neurotoxicity of immunomodulatory drugs in multiple myeloma - Urmeel H. Patel; Muhammad A. Mir; Jeffrey K. Sivik; Divisha Raheja; Manoj K. Pandey; Giampaolo Talamo (Hematology Reports, 2015)
Immunomodulatory drugs (IMiDs) currently used in the treatment of multiple myeloma, are thalidomide, lenalidomide and pomalidomide. One of the most common side effects of thalidomide is neurotoxicity, predominantly in the form of peripheral neuropathy. We report 6 cases of significant central neurotoxicity associated with IMiD therapy. Treatment with thalidomide (1 patient), lenalidomide (4 patients), and pomalidomide (1 patient) was associated with various clinical manifestations of central neurotoxicity, including reversible coma, amnesia, expressive aphasia, and dysarthria. Central neurotoxicity should be recognized as an important side effect of IMiD therapy.